Navigating the broken road: A call to strengthen access, equity, and inclusivity in the care of children with developmental disabilities and neurobehavioral disorders - Aysha Jawed; Christine Peck (Tabriz University of Medical Sciences, 2022)
There is a significant scarcity of resources to achieve behavioral stabilization among children and adolescents with moderate to severe developmental disabilities and neurobehavioral disorders. In total, there are currently 76 inpatient pediatric neurobehavioral programs to support these patients across the United States. Many states do not currently have programs of this nature. Across existing programs, there are substantial waiting lists. In addition, non-public school, intensive day program, in-home and additional outpatient services are not reaching these patients fast enough which further exacerbate the sequalae of suboptimal outcomes and future quality of life implications for these patients. In addition, disparities remain in how the chronicity of developmental disabilities and neurobehavioral disorders are addressed within our healthcare system. It is crucial to categorize this constellation of specialized conditions as chronic illnesses which warrant continued care and treatment, similar in nature to lifelong medical conditions. Further time and priority are warranted in increasing accessibility, equity, and inclusivity in our U.S. healthcare system to optimize a range of health and developmental outcomes for these patients. Future work in this domain could also contribute towards the larger goal of the World Health Organization, Healthy People 2030, and the Sustainable Development Goals of the United Nations in securing delivery of healthcare services that are inclusive, equitable and accessible for individuals with disabilities.